Water supply remote monitoring system: a case study - Ribeiro, Fernando Reinaldo (2011)
In recent years, there has been enormous research interest in natural resources monitoring. So, there is a need to develop easily accessible, cheap and reliable information systems for monitoring and early warning, which could be used in most natural resources. This paper presents an ongoing information system development that aims the monitoring and supervising of some parameters on water supply, such as quality and quantity. To implement our system we use several technologies in order to monitoring about 100 water tanks in an area of ±1000 Km2. In these technologies is included GSM communication, web infrastructure and sensing equipment that allows the access of information from any place of the world. In paper sections the main blocks of the system architecture are described in detail.